The Lehmer matrix with recursive factorial entries - AKKUS, ILKER (Kuwait Journal of Science, 2015)
A generalized Lehmer matrix with recursive entries from Kılıç et al. (2010b) is furthergeneralized, introducing three additional parameters and taking recursive factorials instead ofa term. Certain formulae are derived for the LU and Cholesky factorizations and their inverses,as well as the determinants. Then we precisely compute the elements of the inverse of thegeneralized Lehmer matrix.